Activating transcription factor 4-dependent hsa-miR-663a transcription mediates mTORC1/p70S6K1 signaling underleucine deprivation - Yamamura, Junki; Ma, Sihui; Jia, Huijuan; Kato, Hisanori (Frontiers in Nutrition, 2022)
The mechanistic target of rapamycin complex 1 (mTORC1) is involved in nutrient-induced signaling and is a master regulator of cell growth and metabolism. Amino acid-deficient conditions affect mTORC1 activity; however, its upstream regulators warrant further investigation. MicroRNAs are key regulators of nutrient-related responses; therefore, the present study aimed to assess the leucine starvation-induced microRNA profile and its impact on mTORC1 activity. Transcriptome analysis of human hepatocellular carcinoma cells (HepG2) under leucine deprivation revealed that hsa-miR-663a and hsa-miR-1469 were altered in a transcription factor 4-dependent manner. Overexpression of these microRNAs induced phosphorylation of the ribosomal protein S6 kinase beta-1, a mTORC1 downstream target. Furthermore, hsa-miR-663a downregulated proline-rich Akt1 substrate of 40 kDa (PRAS40), one of the mTORC1 components. In summary, this study provides new insights into the regulatory role of microRNAs in amino acid metabolism and demonstrate alterations in microRNA profile under leucine deprivation in human hepatocytes.